University proceedings. Volga region. Natural sciences - A.Yu. Shishkin; K.A. Shishkina; V.F. Smirnov; N.A. Anikina; T.A. Veselova (Известия высших учебных заведений. Поволжский регион: Естественные науки)
Background. For scientifically substantiated and effective application of new biocidal compounds as means of protecting industrial materials from biodamage, ecophysiological studies are necessary to assess their effect on destructor microorganisms. The purpose of this study was assessing the effect of antimicrobial submicron particles of new photocatalytically active heavy metal oxides on the activity of endo- and exooxidoreductases of fungi – active destructors of industrial materials under dark and visible light conditions. Materials and methods. Fungi were cultivated on nutrient media with enzyme inducers and submicron particles in the dark and under illumination. Enzyme activity was determined spectrophotometrically in the culture liquid and in the mycelium of fungi. Results. The ambiguous effect of submicron particles of newly synthesized complex heavy metal oxides RbTe1.5W0.5O6 and CsTeMoO6, possessing a photocatalytic effect, on the activity of exo- and endooxidoreductases of fungi destructing industrial materials Penicillium cyclopium F-245 and Chaetomium globosum F-109 under dark and visible light conditions was established. There was an increase in the activity of the studied enzymes, both under the influence of light and in the dark in the overwhelming majority. In some variants, the activity of oxidoreductases increased by 8–10 times. Conclusions. Observed effect can be associated with both the physiological and biochemical characteristics of the studied cultures, and with different (dark and light) mechanisms of the inhibitory effect of heavy metal oxides on the metabolism of micromycetes, for instance with ability metal oxide produce different types of reactive oxygen species under light.